Postponement - koncepcja odroczonego różnicowania produktów w łańcuchu dostaw - Bednarz, Leszek (Postponement - concept of delayed product differentiation in supply chain, 2006)
Postponement - means to delay some production or logistical operations until customer order have been received. This increases a company flexibility to respond to demand shiftswith minimal inventory. The paper presents essence and different forms of postponement. Special attention is payed to the analysis of economic, technical and organizational factors, that are crucial in implementing delayed product differentiation in supply chain.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 242-251